The Practices of the Journalism Bias in the Mainstream Online Media in Covering the 2019 Presidential Election - Nurul Hasfi; Wijayanto Wijayanto (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2021)
Objectivity (unbiased) news is an essential journalism principle in covering political news, especially general elections. However, many studies found that violations against these principles were becoming a problem in many elections in different countries. In Indonesia, most research concerns this issue more focusing on the traditional media platform. This article has aimed to explore online media on how they covered the 2019 presidential election. This research combines quantitative and qualitative text analysis methods to investigate 320 online media articles produced by eight leading online media in Indonesia two weeks before the election. By employing the journalism principle of objectivity, the concept of framing and representation, this research found that online media in Indonesia practice biased journalism in reporting the 2019 presidential election. However, each online media has a typical media bias both quantitatively and qualitatively. This study identified two categories of journalism practice, namely partisan journalism that openly supported particular candidates and at the same time attacked the rival. Secondly, the online media category tried to be professional, but they applied journalism bias by construction framing strategy and representation for the candidate they supported. This research also highlights that the bias of online media journalism was facilitated by the general principle of digital journalism routine in Indonesia that mostly focuses on speed rather than on comprehensive information and also facilitated by the existence of the hyper-link feature that legitimizes the 'cover one side' in a single article.